CONTROLLING CONSTRUCTION’S TIME AND COST OF PUSKESMAS WITH EARNED VALUE METHOD - M. Fanshurullah Asa; Anjelita Carmelitas Borges (Jurnal Ilmiah Teknik Sipil, 2024)
On a project there are always some problems there are caused by cost and time. In the implementation of projects it is very rare that it can go exactly as planned. In avoiding losses in development work activities, cost and time control is used with a concept commonly called the Earned Value concept method. The purpose of writing this paper is to analyze the cost and time performance in completing the Lumbang Puskesmas Building project, Kabupaten Probolinggo using the Earned Value method. The performance results of project implementation based on the concept of earned value from ACWP are Rp. 4,624,935,401, BCWS and BCWP values are Rp. 4,624,935,404. based on the ACWP, BCWS and BCWP values, the value of Cost Variance (CV) is Rp 3.40 and Schedule Variance (SV) is equal to zero. The values of SPI and CPI are equal to 1. The estimated project completion time is 150 days which is the same as the project plan time. The estimated final cost of the project is Rp. 4,624,935,397 which shows that the costs incurred are smaller than the total budget plan (BAC) of Rp. 4,624,935,404. As a result of these calculations, the project did not experience delays or additional costs.